Several Methods to Teach Reading to Early Childhood - Vera Sri Wahyuni (International Journal of Ethno-Sciences and Education Research, 2021)
One of the challenges now faced by the parents of young children, especially at the early childhood level of education is to teach reading. This paper aims to find out some more effective ways to teach reading to the children. The method discussed in this paper include: using children’s songs and books, using game card , through guessing game, using variety of study applications, and the parent’s patience. The results of the study show that in order to teach reading to early childhood, the parent or teacher must be able to choose a method that suits the child's situation, abilities and interests. Thus, it will able to increase children's ability and interest in reading and avoid boredom.